Screening for the gene (GM1, GM4, GM11) disease gall midge re-sistance genes in Oryza sativa L cultivar using molecular indicators SSR - Th. Abdul- Hussain AL-Refeay, Z.; Ab.H. Messan Al–Badeiry, N. (Journal of Kerbala for Agricultural Sciences, 2018)
Orseolia oryzae one dangerous pests that cause a great loss to the Oryza sativa L. crop, used markers Simple Sequence Repeats based polymerization reactions chained to the detection of resistance genes to disease. the DNA isolate of rice leaves after 25 days from sowing .using Genomic DNA plant kit Protocol to extraction , the amount of DNA in good range (125-589) ng / μl purity of 08.01 to 09.01. migrated samples on the gel akaros after completing the PCR program results showed three primers with sixteen cultivar ,The range of molecular size between (1156.84-197.768bp).the primer RM23956 reached to highest number of 16 alleles While the lowest number of 11 alleles recorded RM28574 primers. The Polymorphism information content (PIC) which is a reflection of the diversity of allelic and repetition allelic between varieties ranged value between ((0.8807-0.9837. As ranged gene diversity values ​​between 0.8906- 0.9772. the primers RM23956 which reveals gane GM1 in twelve genotypes followed by the RM28574 which reveals gane GM11 in seven genotypes either the primers RM547 which reveals gane GM4 in five genotypes, as the results showed that the abaa1 cultivars of the contains three genes